(Tomme) NPer i moderne generativ syntaktisk teori (2. del) - Jacobsen, Bent (HERMES - Journal of Language and Communication in Business, 1989)
The present paper takes its point of departure in the concept of empty NP-categories, as this is embodied in a more comprehensive theory of NPs. The theoretical framework adopted is mainly that expouned in Chomsky: Lextures on Government and Binding (1981) and subsequent works (though no attempt has been made to incorporate the revised model presented in Chomsky: Barriers (1986)). The paper gives a brief introduction to the main modules of a modern generative grammar (X-bar syntax;0-theory; government (including proper government and the Extended Empty Category Principle); the theory of abstract Case; the theory of Binding; and the theory of Bouding). The paper falls into two parts. In the first part the basic modules and principles are introduced. In the second part, to be published in the next issue of Hermes, it will be shown how these modules interact in the derivation of sentences. Particular attention will be paid to NP-Movement and Wh-Movement. A separate section will deal with the status of PRO. The full bibliography appears after both parts.